2017
DOI: 10.1111/ffe.12733
|View full text |Cite
|
Sign up to set email alerts
|

Modes I/II SIF of a diametrically compressed Brazilian disc having a central inclined crack with frictional surfaces

Abstract: An in‐house finite element code was used to analyse a diametrically compressed isotropic homogeneous Brazilian disc having a central inclined crack with frictional surfaces for the evaluation of its corresponding modes I and II stress intensity factor (SIF). One‐half of the disc was successfully idealized. The coefficient of friction between the crack surfaces ranged from 0 to 1 in steps of 0.1. Relative crack length ratios of 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, and 0.7 were analysed with crack angles up to 90° in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…Instead, a fine mesh was constructed around the crack tip. That idealization proved its adequacy in similar analyses (Hammouda et al, 2002(Hammouda et al, , 2003a(Hammouda et al, , 2003b(Hammouda et al, , 2004(Hammouda et al, , 2007(Hammouda et al, , 2017Fayed, 2008;Fayed et al, 2008).…”
Section: S 2rmentioning
confidence: 77%
See 1 more Smart Citation
“…Instead, a fine mesh was constructed around the crack tip. That idealization proved its adequacy in similar analyses (Hammouda et al, 2002(Hammouda et al, , 2003a(Hammouda et al, , 2003b(Hammouda et al, , 2004(Hammouda et al, , 2007(Hammouda et al, , 2017Fayed, 2008;Fayed et al, 2008).…”
Section: S 2rmentioning
confidence: 77%
“…Hammouda and Fayed (2017) found that da/a = 0.008 was sufficient to get an accurate solution for their problem. The ratio da/a in the present work was decided based on the results of similar pilot exercises in which the several da/a ratios 0.002, 0.004, 0.006 and 0.008 were also invoked to compare the resulting computed stress intensity factors.…”
Section: S 2rmentioning
confidence: 99%
“…The determination of relevant SIFs is the main objective of related numerical and analytical works. The numerical methods include the finite element method, 16–20 the boundary element method, 21,22 the discrete element method, 23 and the finite difference technique 12 . That led to some analytical and numerical solutions for those disc systems.…”
Section: Introductionmentioning
confidence: 99%
“…Pure mode II SIF exists in the case of having the crack tip closed with sliding crack surfaces. In case of frictional crack surfaces, crack tip can be in a sticking contact mode leading to zero K II 13,17 . Researchers have paid attention both numerically and analytically in addressing closed cracks having pure mode II operating with either smooth or frictional crack surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…3 During the past decades, various methods and solutions have been proposed to obtain SIFs for the cracked discs subjected to various boundary conditions. [4][5][6][7][8][9][10][11][12] Using the dislocation method, an important and closed-form SIF solution was given by Atkinson et al, 5 for the centrecracked disc subjected to diametrically concentrated compressive forces. The explicit SIFs for several crack lengths and crack inclinations were given in the form of infinite series.…”
Section: Introductionmentioning
confidence: 99%